Implementasi Digital PR Pada Um Buton Dalam Menyebarkan Informasi Publik - Muhammad Rizal Ardiansah Putra Ardiansah; Muhammad Hidayatullah (CV. ITTC INDONESIA, 2021)
Cyber Public Relations is a public relations endeavor that uses the internet as a medium for publication in order to improve reputation on a national and international level. As a result of intense competition in the digital world, universities must continue to compete in providing information to the public. In this context, UM Buton's online public relations efforts are the most crucial. This research was conducted using a qualitative, descriptive research method. For the purpose of identifying, analyzing, and evaluating the University of Muhammadiyah Buton's cyber public relations operations to date, this study seeks to do research in this area. On the official website of the University of Muhammadiyah Buton, cyber public relations activities include press releases, collaborations, online journals, siakad, films, and information providers. In addition, another supporting factor is the use of social media. Since the power of social media in gathering opinions in cyberspace has begun to be recognized by many parties, it is not surprising that an institutional brand can be both well-imaged and ruined through opinion-raising via social media. By boosting UM Buton's public relations cyber efforts, this institution is able to compete on the internet. Researchers hope that this study will serve as a review and feedback so that the University of Muhammadiyah Buton can improve its cyber public relations operations so that it can compete on a national and international scale.